2020
DOI: 10.1177/1758835920967237
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab treatment in advanced non-small cell lung cancer: real-world long-term outcomes within overall and special populations (the UNIVOC study)

Abstract: Objective: To describe long-term outcomes of patients treated with nivolumab for advanced non-small cell lung cancer (aNSCLC) in everyday clinical practice in France, with a focus on patients aged ⩾80 years, patients with renal impairment and patients with brain metastases. Methods: The study included all patients with aNSCLC recorded in the French national hospital database, starting nivolumab in 2015–2016 and followed until December 2018. Patients were stratified by age, the presence of renal impairment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Various studies based on the nivolumab Italian expanded access program focused on the subgroup of patients with brain metastases, showing similar efficacy of nivolumab compared with the overall population, with a 1-year OS rate of 43% [30][31][32][33]. Analogous results were reported in the real-world UNIVOC study, which reported a 2-year OS rate of 28.5% (26.4-30.8) in patients with brain metastases compared with 30.0% (29.0-31.1) in those without [34]. Likewise, data from a real-world pooled analysis of NSCLC patients from Canada, France, and Germany treated with nivolumab did not show significant differences in terms of OS, with a 1-year OS rate of 44% in the subgroup of brain metastases vs. 50% in that without CNS involvement [35].…”
Section: Single-agent Anti-pd-l1/pd-1 or Anti-ctla-4 Monoclonal Antib...mentioning
confidence: 67%
“…Various studies based on the nivolumab Italian expanded access program focused on the subgroup of patients with brain metastases, showing similar efficacy of nivolumab compared with the overall population, with a 1-year OS rate of 43% [30][31][32][33]. Analogous results were reported in the real-world UNIVOC study, which reported a 2-year OS rate of 28.5% (26.4-30.8) in patients with brain metastases compared with 30.0% (29.0-31.1) in those without [34]. Likewise, data from a real-world pooled analysis of NSCLC patients from Canada, France, and Germany treated with nivolumab did not show significant differences in terms of OS, with a 1-year OS rate of 44% in the subgroup of brain metastases vs. 50% in that without CNS involvement [35].…”
Section: Single-agent Anti-pd-l1/pd-1 or Anti-ctla-4 Monoclonal Antib...mentioning
confidence: 67%
“…Unlike standard therapies, which act to slow tumor growth and metastasis, ICIs offer significant benefits on the tumor eradication and long-term remission (4). In clinical trials, to date, as well as in real-world studies, ICIs have demonstrated their efficacy in extending overall survival (OS) compared to standard therapies (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…The study design and patient identification process have been published elsewhere 4,7 and are summarized here. This was a retrospective observational study on the basis of the PMSI database, which includes records for patients receiving outpatient anticancer treatment infusions.…”
Section: Methodsmentioning
confidence: 99%
“…Real-world studies also explored nivolumab outcomes for subgroups of patients (elderly patients with brain metastases or renal impairment) and demonstrated overall survival (OS) benefit. 4 . In patients treated with nivolumab in second-line setting or later, almost half receive another treatment line after nivolumab 6 and a substantial proportion is retreated with nivolumab after a treatment-free interval or chemotherapy.…”
Section: Introductionmentioning
confidence: 99%